Last- Mile Logistics Concepts Intensify The E- Commerce Growth Among The Consumer In Perak, Malaysia - Mohan,; SPR, Charles Ramendran; Anthony, Clarence; Singh, Ninderpal (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this paper is to examine the consumer’s satisfaction towards the last mile logistics (LML) in e-commerce business. In LML, consumer satisfaction is the main concern and it is influenced by variety of factors which include reliability, flexibility, consumer attitude and technology. A systematic literature review being examine the interface between e-commerce and last mile logistics. Followed by a quantitative analysis methodology to understand the significant status of variables where ta survey being conducted within a discipline manner. The findings are supported with a literature analysis conceptualizes between a set of variables. The authors propose that the future research should be focused on the economic growth of e-commerce and last mile logistics in Malaysia. To circumvent the restraint of this research, the authors expand the examining of research to derive the states of consumers. The framework of this research specifies the insights of last mile logistics service that supports the complete e-commerce accomplishment. Improved consumer satisfaction would have a positive impact in term of last mile logistics services and e-commerce. Lastly, this paper comprehensively reviews on LML, which is very essential to fulfill consumer requirements to adapt the e-commerce trend.